IMMU-07. "STROKE MIMICS" ARE NOT BENIGN IN IMMUNOCOMPROMISED CHILDREN. (1st June 2021) - Mahdi, Jasia; Bach, Alicia; Smith, Alyssa; Tomko, Stuart; Fields, Melanie; Griffith, Jennifer; Morris, Stephanie; Guerriero, Rejean; Noetzel, Michael; Guilliams, Kristin; Agner, Shannon
Abstract: Objective: To determine the clinical variances between strokes and stroke mimics in a pediatric immunocompromised population that consists of children with central nervous system (CNS) and non-CNS malignancies and a history of solid organ transplantation. Methods: We performed a retrospective cohort analysis of stroke alert activations in patients with high-grade gliomas, low-grade gliomas, atypical teratoid rhabdoid tumors, rare CNS tumors, B-cell acute lymphoblastic leukemia, T-cell acute lymphoblastic leukemia, osteosarcoma, and solid organ transplants at St. Louis Children's Hospital between February 2013 and September 2019. We categorized final diagnoses as strokes or stroke mimics. We classified diagnoses as a neurologic emergency if the diagnosis necessitated changes in management. Results: Out of 217 stroke alerts, 31 alerts occurred for 28 patients meeting inclusion criteria. All final diagnoses constituted neurologic emergencies, including: stroke (39%), chemotherapy-related neurotoxicity (29%), tumor progression (19%), and seizures/posterior reversible encephalopathy syndrome (13%). Patients meeting inclusion criteria with strokes and stroke mimics presented similarly, with the exception of altered mental status, which was more prevalent in patients with strokes than stroke mimics (p = 0.03). One child received hyperacute thrombectomy for stroke. Only 58% of children with stroke mimics had complete resolution of their presenting neurologic symptoms. Children with strokes and stroke mimics had similar mortality incidences of 33% and 37%, respectively. Conclusions: Although all acute neurologic changes in immunocompromised children are not strokes, stroke mimics in this population are neither benign nor self-limited and carry long-term neurologic morbidity and mortality. This study highlights the utility of an acute stroke evaluation infrastructure and the need for acute and long-term neurology involvement in the care of these patients.